Application of Terrestrial Laser Scanning and 3D Finite Element Analysis to Safety Assessment of a Roller-Compacted Concrete Dam During Operation - Pham, Nguyen Hoang; Do, Tuan-Nghia; Nguyen, Lan Chau (Indonesian Geotechnical Journal, 2025)
This paper presents the combination of terrestrial laser scanning (TLS) and 3D finite element analysis to assess safety of a roller-compacted concrete (RCC) dam. The investigated case is the Ban Lai dam, located in Lang Son province, Vietnam. The deformations of the dam surface at three different storage water levels were firstly scanned by point cloud through TLS and then back analyzed using the 3D finite element software (Plaxis). The numerical analysis was adopted to calculate vertical normal stress and horizontal normal stress along the stream direction caused by the dam deformation in order to assess its safety during operation. Results showed that the dam surface’s deformations by the numerical analysis and TLS were very close to each other and also approximate to those of total station. When the storage water level rose, both the maximum (tensile) normal stresses and the minimum (compressive) normal stresses decreased but the dam remained at a safe state. The constructed relationship between the vertical and horizontal normal stresses with the storage water level could help to roughly determine the normal stress corresponding to any storage water level and judge the safety of the dam. Finally, a flow chart of the integration between TLS and 3D finite element analysis was proposed to assess dam safety for other cases.